A COMPARATIVE EFFECT OF SELF ASSESSMENT COMBINED WITH STUDENTS’ AND TEACHERS’ FEEDBACKS ON THE STUDENTS’ WRITING COMPETENCY BASED ON TEXT TYPES IN SMA N 4 SINGARAJA. - Dyutami Maharani, Nyoman; Tantra, Dw. Komang; Artini, Luh Putu (Jurnal Pendidikan Bahasa Inggris Indonesia, 2013)
Abstract This study aimed at comparing the effect of Self-Assessment combined with students? and teachers? feedback on students? writing competency based on text types in SMA N 4 Singaraja. The research design is Post-test only comparison group design with 2x3 Factorial Design. This study is an experimental research which is involving three variables. The first variable is independent variable, that is, Self-Assessment (A) with two levels namely Self-Assessment with Students? Feedback and Self-Assessment with Teachers? Feedback. The second variable is the moderator variable that is text types (B) with three levels namely Descriptive, Narrative, and News Item. The third variable is the dependent variable, that is, Writing Competency (Y). From the result of the study it could be conclude that writing competency of students who were taught using self-assessment combined with teacher feedback is better than those who were taught using self-assessment combined with students? feedback. Therefore, the first conclusion which can be made from this research is self-assessment combined with teacher feedback which was used to treat the students of X2 grade students of SMA N 4 Singaraja can affect better toward students? writing competency than the self-assessment combined with students? feedback which was used to treat the students of X3 grade students. Considering the variable of text type in writing, it was found that, narrative text was the higher score among the three text type in both students who were taught using self-assessment combined with teachers? feedback and students who were taught using self-assessment combined with students? feedback.   Key words: writing competency, self-assessment, feedback and text type